Growth Performance, Body Conformation, Carcass Characteristics And Palatability Of Kedah-Kelantan Catle And Its Crosses - Ismail, Dahlan (1985)
The growth performance of 423 heads of male and female Kedah-Kelantan ( KK ) cattle and its F1 crosses were recorded from the same grazing management. Comparisons were made between progenies of KK cows sired by straightbred KK, American Brahman (Br), Polled Hereford (Hr), Friesian (Fr) and Jersey (Jy). The wain objectives of this experiment was to evaluate the simplest crossbreeding system of KK cattle by straight cross between KK female and exotic male for the advantage of heterosis in the growth performance, conformation, carcass characteristics and meat palatability in the F1 generation. The present result showed that all the F1 crossbreds heifers and bulls were superior in the growth performance D1an the straightbred KK at all ages. All crossbred calves had significantly higher (P < 0.01 ) birth weight than KK. 3rahrnan x KK ( BK ) calves were the heaviest at birth, followed by Friesian x KK ( FK ) , Hereford x KK ( HK ) and Jersey x KK (JK), resp2Ctively. The overall percent advantage of crossbreds at birth weight over KK was 27.13%. FK was the heaviest at the adjusted 200-day weight, followed by HK , BK, JK and KK respectively. All crossbreds calves were showing better pre-weaning growth ability than the KK. HK showed superiority in post weaning growth performance than the other crossbreds. Ranking of sire breeds by using the slope of regression equation of growth-age lines as the estimate of growth rate, generally showed consistent for the breedtype among years. Under similar management unit and one type of maternal environment , the result showed that bleed. sire , especially temperate sires , had contributed the main effect on all the growth traits of these calves.